De La Mettrie's Ghost The Story Of Decisions - Nunn, C. (Macmillan Science, 2005)
This book is about how we make choices. Drawing together evidence from 21st century chemistry to Victorian politics, enlightenment philosophy, Roman drama and beyond, it is a compelling hunt for the nature of free will.